Lire le « désastre » chez Maurice Blanchot : Une poétique du temps et de l'histoire. Issue 2 (14th March 2020) - Azoulay, David
Abstract: This article analyzes the notion of "disaster" in Maurice Blanchot's work in order to understand how it brings into play a poetics of time and history in his writing. Starting from an interpretation of an allegory of Kafka by Hannah Arendt, our article first aims to highlight his notion of "disaster, " as embodied in the critical practice of Blanchot. In his reading of Kafka's work, Blanchot makes of it a "legacy without a will, " which suggests how his own conception of modern literature is marked by a fragmentation of temporality. Based on this observation, the last part of the article proposes to highlight the historicity of the concept of "disaster" in order to show how it modulates his reading of modern literature and his conception of time and history.